1999
DOI: 10.1063/1.371726
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation on AlGaN thin films

Abstract: Hardness and Young’s modulus were measured in AlGaN thin films with different Al content, using a nanoindentation technique. Hardness slightly decreases with increasing Al content, ranging from 20.2 to 19.5 GPa for Al content from 0.09 to 0.27, respectively. No significant variations of Young’s modulus were observed. The resulting value of Young’s modulus is 375 GPa. Discontinuities in load–displacement curves were found, which are associated with dislocation nucleation. The threshold load for this discontinui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 17 publications
8
22
1
Order By: Relevance
“…Shi et al [398] have detected 180% increase of both the hardness and Young's modulus of the bulk value of amorphous carbon thin films deposited on silicon substrate. Caceres et al [361] have also observed the similar enhancement of both the Young's modulus and the hardness at an AlGaN surface.…”
Section: Surface Stress and Young's Modulusmentioning
confidence: 55%
See 1 more Smart Citation
“…Shi et al [398] have detected 180% increase of both the hardness and Young's modulus of the bulk value of amorphous carbon thin films deposited on silicon substrate. Caceres et al [361] have also observed the similar enhancement of both the Young's modulus and the hardness at an AlGaN surface.…”
Section: Surface Stress and Young's Modulusmentioning
confidence: 55%
“…32(b) confirm the predictions of high elasticity of the nitride surfaces contributed by the lone pair interaction. For GaAlN film [361], the elastic recovery is as high as 100% under lower indentation load (0.7 mN) compared with that of amorphous carbon film. The GaAlN surface is also harder than the a-C film under the lower indentation load.…”
Section: Confirmation: Ultra-elasticity Of Nitride Surfacesmentioning
confidence: 95%
“…An examination of the hardness (also stress) and the Young's modulus using nanoindentation revealed that the surface of the TiCrN thin film (2 mm thick) is 100% higher than its bulk value [136]. The same trend holds for amorphous carbon [209] and AlGaN surfaces [210]. Ni films also show maximal hardness in w5 nm depth of the surface, though the peak maxima vary with the shapes of nanoindentor tips [211].…”
Section: 122mentioning
confidence: 90%
“…The thickness dependence of both the Y and the P follows a similar . Nanoindentation hardnessedepth profile for TiCrN [136] and GaAlN [210] thin films. The peak shift corresponds to the surface roughness (Ra ¼ 10 nm as confirmed by AFM).…”
Section: 122mentioning
confidence: 99%
“…The bias-induced stress of 0.3 GPa is well below the critical resolved sheer stress value of 3.3 GPa or higher [34]- [37] needed to cause lattice disruption and defect formation. However, we calculate the built-in stress due to Al 0.25 Ga 0.75 N/GaN lattice mismatch to be 2.7 GPa, similar to other recent calculations [11].…”
Section: Discussionmentioning
confidence: 82%